Separate and joint associations of chronic pain, multisite pain and mental health with sickness absence among younger employees: a register based longitudinal study - Pi Fagerlund; Rahman Shiri; Johanna Suur-Uski; Sara Kaartinen; Ossi Rahkonen; Tea Lallukka (BMC, 2023)
Abstract Background Pain conditions and poorer mental health are associated with work disability. However, few studies have examined the association of concurrent pain and poorer mental health with sickness absence among younger employees. We examined separate and joint associations of chronic pain, multisite pain, and mental health with total and long-term all-cause sickness absence days among younger Finnish municipal employees. Methods The Young Helsinki Health-study data were collected in 2017 from 19-39-year-old employees of the City of Helsinki, Finland. Chronic (≥ 3 months) and multisite (≥ 2 body sites) pain and mental health (RAND-36 emotional wellbeing subscale dichotomized by median score) were self-reported (n = 3911). Chronic pain, multisite pain and mental health were analyzed separately and combined. Register data on total (≥ 1 workdays) and long-term (≥ 11 workdays) sickness absence days during the following year were obtained. Negative binomial regression analyses were performed with sociodemographic, socioeconomic, and health-related factors as confounders. Gender interaction and synergistic indices were examined. Results Chronic multisite pain was associated with long-term sickness absence days (rate ratio [RR] 2.51, 95% CI 1.17-5.42). Chronic pain (RR 5.04, 95% CI 2.14-11.87) and multisite pain (RR 4.88, 95% CI 2.30-10.33) were associated with long-term sickness absence days among employees with poorer mental health. There was a synergistic interaction between gender and multisite pain for total sickness absence days (synergy index 1.80, 95% CI 1.27-2.54), with stronger associations among women. Conclusions Chronic and multisite pain are associated with long-term sickness absence among younger employees, particularly among women and employees with concurrent poorer mental health. Consideration of this knowledge at workplaces and in healthcare could help to identify and support employees at increased risk of later sickness absence.